The nest [videorecording (DVD)] - Durkin, Sean; Law, Jude, 1972-; Coon, Carrie, 1981-; Shotwell, Charlie; Roche, Oona (IFC Films/Shout Factory, 2021)
Rory, an ambitious entrepreneur, and former commodities broker persuades his American wife, Allison, and their children to leave the comforts of suburban America and return to his native England during the '80s. Sensing an opportunity, Rory rejoins his former firm and leases a centuries-old country manor, with grounds for Allison's horses and plans to build a stable. Soon the promise of a lucrative new beginning starts to unravel, the couple has to face the unwelcome truths lying beneath the surface of their marriage.